Inferential narrative comprehension ability of young school-age children on the autism spectrum. (July 2021) - Westerveld, Marleen F; Filiatrault-Veilleux, Pamela; Paynter, Jessica
Background and aims: The purpose of the current exploratory study was to describe the inferential narrative comprehension skills of young school-age children on the autism spectrum who, as a group, are at high risk of significant and persistent reading comprehension difficulties. Our aim was to investigate whether the anticipated difficulties in inferential narrative comprehension in the group of children with autism could be explained by the children's structural language ability as measured using a broad-spectrum standardized language test. Methods: The participants were 35 children with a diagnosis of autism spectrum disorder (ASD), aged between 5;7 and 6;11, who attended their first year of formal schooling, and 32 typically developing (TD) children, matched to the ASD group for age and year of schooling. Children on the autism spectrum were divided into below normal limits (ASD_BNL, standard score ≤80; n  = 21) or within normal limits (ASD_WNL, standard score >80; n  = 14) on a standardized language test. All children participated in a narrative comprehension task, which involved listening to a novel story, while looking at pictures, and answering eight comprehension questions immediately afterwards. Comprehension questions were categorized into factual and inferential questions, with further categorization of the inferential questions into those tapping into the story characters' internal responses (mental states) or not. Children's responses were scored on a quality continuum (from 0: inadequate/off topic to 3: expected/correct). Results: Our results showed significantly lower scores across factual and inferential narrative comprehension in the ASD_BNL group, compared to the ASD_WNL and TD groups, supporting the importance of structural language skills for narrative comprehension. Furthermore, the TD group significantly outperformed the children in the ASD_WNL group on inferential comprehension. Finally, the children in the ASD_WNL group showed specific difficulties in answering the internal response inferential questions compared to their TD peers. Conclusions: Results from this exploratory study highlight the difficulties children on the autism spectrum may have in inferential narrative comprehension skills, regardless of sufficient structural language skills at word and sentence level. These findings support the importance of routinely assessing these narrative comprehension skills in children on the spectrum, who as a group are at high risk of persistent reading comprehension difficulties. Implications: In this study, we demonstrate how narrative comprehension can be assessed in young school-age children on the autism spectrum. The scoring system used to categorize children's responses may further assist in understanding children's performance, across a quality continuum, which can guide detailed goal setting and assist in early targeted intervention planning.